Landslide hazard prediction and impact on comminity: main approaches, principles and methods - Ivanik, O.; Shevchuk, V.; Kravchenko, D.; Hadiatska, К. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problem of predicting the landslide hazard is a priority area of research in the field of assessment of risks and natural disasters, which requires a comprehensive in-depth analysis of the factors of landslide formation, as well as the synthesis of existed theorethical and empiric data for a full understanding of the problem of landslide hazard and comprehensive assessment of its impact on community. The presented research is aimed at the development, implementation, and application of a comprehensive methodology for predicting landslide hazards and assessing their impact on the infrustructure. The research was carried out within the framework of national and international projects with the partiсipation of internationalpartners from universities in France, Austria and Great Britain. The methodology of regional landslide hazard prediction for different structural regions of Ukraine is based on the methods of spatial modelling and aims at the landslide susseptibility mapping, creating multifactorial spatial models. As a result of a comprehensive analysis of landslide factors and spatial modelling integrated landslide hazard maps were created. These maps provide an opportunity to comprehensively assess the landslide hazard for different regions. Methods of local prediction of landslide hazard based on the application of a rational complex of geological, physical, remote, thermographic studies, and deterministic modelling enable to identify the main features and potential activity of landslide processes within landslide-prone areas and suggest preventive measures for risk mitigation. Examples of the integrated methodology applications for landslide hazard prediction within model sites in Kaniv and Kyiv regions are given. The concept of informing people about the potential geohazards was given.
Keywords: landslide hazard; slope stability; forecast; deterministic modelling